2000
DOI: 10.1161/01.atv.20.12.2527
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinases Mediate Matrix Metalloproteinase-9 Expression in Vascular Smooth Muscle Cells

Abstract: Abstract-Expression of matrix metalloproteinase (MMP)-9 has been linked to the progression of plaque rupture and intimal formation in arterial lesions. In this study, we determined which factors and signaling pathways are involved in regulating the MMP-9 gene. Rat carotid arterial smooth muscle cells treated with tumor necrosis factor (TNF)-␣ showed a marked increase in MMP-9 activity and mRNA level, whereas platelet-derived growth factor (PDGF) showed a slight induction of the MMP-9 mRNA level. TNF-␣ treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
135
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(146 citation statements)
references
References 29 publications
8
135
0
3
Order By: Relevance
“…Inhibition of Erk-MAP kinase pathway has been shown to affect the expression of serine proteinase uPA (De Kier Joffe et al, 2000) and metalloproteinase MMP-9 (Cho et al, 2000). We have recently shown that activation of Erk is critical for plasminogen-dependent matrix degradation mediated by pro-uPA and pro-MMP-9 (Ahmed et al, 2002b).…”
Section: Discussionmentioning
confidence: 92%
“…Inhibition of Erk-MAP kinase pathway has been shown to affect the expression of serine proteinase uPA (De Kier Joffe et al, 2000) and metalloproteinase MMP-9 (Cho et al, 2000). We have recently shown that activation of Erk is critical for plasminogen-dependent matrix degradation mediated by pro-uPA and pro-MMP-9 (Ahmed et al, 2002b).…”
Section: Discussionmentioning
confidence: 92%
“…Especially, MMP-9 is a crucial enzyme for regulating the migration and proliferation of VSMCs (Galis et al 2002). The release of MMP-9, which was expressed upon treatment with TNF-a, was also reported to be mediated by transcriptional factors such as NF-jB and AP-1 via activation of the Ras/ERK pathways (Cho et al 2000;Moon et al, 2003Moon et al, , 2004. MMP-2 and MMP-9 especially play pathogenic roles in the development of vascular remodeling by degrading various components of the ECM, and allowing invasion of collagen into the intimal layer (Rodriguez et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The proposed role of MAPK signaling in the upregulation of LMP2A expression and an increased metastasis rate remains controversial [20]. It has been shown that the ERK/MAPK pathway is involved in cell migration and tumor progression [115][116][117][118][119]. In the three-dimensional collagen gel assay, LMP2A expression renders migratory ability, and promotes the mobility of EBV-infected NPC cell lines [20].…”
Section: Mapk Pathwaymentioning
confidence: 99%